Predicting the success of intrauterine insemination using a clinically based scoring system - Rajaraman, Sowbarnika; Shankar, Kundavi; V., Geetha; Asokan, Yamini; G. V., Rashmi; Ranji, Geovin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Aim of the study was to predict the success of intrauterine insemination (IUI) using a clinically based scoring system. Retrospective cohort study in the institute of reproductive medicine, the Madras medical mission, Chennai Methods: The 240 patients meeting the inclusion criteria and exclusion criteria who underwent IUI with husband/ donor sperms were retrospectively assessed. 10 parameters each influencing the success of IUI were taken and a total score was derived for each patient and their predictive cut off for success of IUI was determined. Each factor was also analysed individually for the success of IUI. All the patients were followed up till their serum beta human chorionic gonadotropin (hCG) test done 16 days post insemination. Results: On evaluating, ROC curve was obtained and it showed that a cut off of 13.5 had a success prediction post IUI with a sensitivity of 82.9 and specificity of 68.2 on individually analyzing the 10 factors, serum anti-Müllerian hormone (AMH) was found to be influence the success of IUI. Conclusions: The proposed scoring system integrates the parameters to provide an individualized pregnancy probability estimate. This tool can support clinicians in counselling patients more effectively, aiding in decision making and setting realistic expectations.